Effectiveness of a menstrual health education program on psychological well-being and behavioral change among adolescent girls in rural Uganda - Yi-Ting Yang; Duan-Rung Chen (AOSIS, 2023)
Objectives: Menstrual hygiene management is one of the main barriers to girls' education attainment in low-and middle-income countries. Poor access to sanitary products and lack of menstrual knowledge affect students' performance at school compared to the opposite sex. Limited evidence is available to provide solutions for schoolgirls. This study examines the effectiveness of menstrual health education programs on well-being and behavioral change among adolescent girls in rural Uganda. Methods: A cluster randomized controlled trial was conducted across 3 schools, including 66 girls aged 13-17 years, in a rural village in Mukono District, Uganda. Schools were randomly allocated to 2 groups: i) health education program intervention and ii) control group (no intervention). Results: After 5 weeks of the Health Education Program, the schoolgirls in experiment groups showed significantly less fear of sharing the menstruation-related concern with parents and pupils [Mean Difference (MD)=0.87, P=0.029) (MD=2.02, P=0.000), and the sense of shameful feelings during menstruation (MD=1.65, P= 0.004); conversely, the fear to go to school during menstruation did not differ between experiment and control groups (MD=-0.04, P=0.94). However, the changes in feeling comfortable having a period at school were significantly different between the experiment and control groups (P=0.001). Conclusions: The study demonstrated promising results of a low-cost intervention for enhancing girls' menstrual health education in a low-income context. Puberty education and reusable pad sewing provision were strongly associated with improving schoolgirls' psychosocial wellbeing related to menstrual management.